1970
DOI: 10.1254/jjp.20.102
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Action of N-Ethoxycarbonyl-3-Morpholinosydnonimine, Sin-10

Abstract: The studies on structure and action of 3-substituted sydnonimines and their ring opened derivatives (1, 2) indicated that hypotensive action induced by the compounds was closely related to the chemical stabilities of their sydnonimine rings and ring-opened derivatives. That is, a ring-opened derivative of 3-morpholinosydnonimine hydrochloride (SIN-1), N-nitroso-N-morpholinoaminoacetonitrile (SIN-IA), is unstable but a rapid acting and very potent vasodilator comparable to nitroglycerin. On the other hand, N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1
4

Year Published

1970
1970
1990
1990

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 10 publications
0
6
1
4
Order By: Relevance
“…SIN-10, N-acylated and chemically stable derivative of SIN-1, showed gradually developed and prolonged hypotension which was characterized by decrease in pulse pressure resulting from more depression during systole than during diastole. In constant flow perfusion experi ments, SIN-10 decreased slightly the perfusion pressure of the coronary artery, but decreased the total coronary inflow in association with the fall of systemic blood pressure in auto perfusion experiments (5). In the present study, RP was not affected in spite of the hypotension by intravenous 100 and 250 ag/kg of SIN-10, although RF did not consistently increase.…”
Section: Discussioncontrasting
confidence: 48%
“…SIN-10, N-acylated and chemically stable derivative of SIN-1, showed gradually developed and prolonged hypotension which was characterized by decrease in pulse pressure resulting from more depression during systole than during diastole. In constant flow perfusion experi ments, SIN-10 decreased slightly the perfusion pressure of the coronary artery, but decreased the total coronary inflow in association with the fall of systemic blood pressure in auto perfusion experiments (5). In the present study, RP was not affected in spite of the hypotension by intravenous 100 and 250 ag/kg of SIN-10, although RF did not consistently increase.…”
Section: Discussioncontrasting
confidence: 48%
“…The hemodynamic response to molsidomine in patients with un complicated myocardial infarction is charac terized by a marked reduction in right atrial and pulmonary capillary wedge pressures [ 10], which suggests that there is probably a concomitant reduction in ventricular dia stolic volumes. Indeed, a number of experi mental [16,20,21] and clinical studies [5,7,9,22] have suggested a pronounced and sus tained venodilating activity of molsidomine, which is associated with decreased ventricu lar filling pressures as well as decreased dia stolic and systolic ventricular dimensions. Thus, it is probable that molsidomine causes more reduction of left ventricular wall ten sion and further decrease in myocardial oxy gen requirements than can be explained by the fall in arterial pressure alone.…”
Section: Discussionmentioning
confidence: 99%
“…Tierexperimentelle Ergebnisse weisen auf einen nitroähnlichen Wirkungsmechanismus hin (3,8,9,18). Eine Dosis von 2 mg oral oder sublingual ist beim Menschen etwa 6 Stunden lang antianginös wirksam, das Wirkungsmaximum ist eine halbe Stunde bis 4 Stunden nach Einnahme erreicht (7,12,16,19 o---e…”
Section: üBer Den Wirkungsmechanismus Bestehen Bei Einigenunclassified